Factor that influence job satisfaction at Majlis Daerah Tampin / Nur Shafarina Shafie - Shafie, Nur Shafarina (Faculty of Business and Management, 2017)
This study tries to determine the level of job satisfaction and identify the relationship between job satisfaction and job satisfaction components which are working environment, compensation and benefit, employee engagement and employee empowerment among employees in Majlis Daerah Tampin. The study was conducted among 115 respondents in Majlis Daerah Tampin. In this study, the whole population method was used. This study could make important contribution to extant research in management and organizational behaviour. The result showed that working environment, compensation and benefit, employee engagement and employee empowerment have significant and positive relationship towards job satisfaction. Besides that, the result also proved that employee engagement is the most influence factor on job satisfaction which give 22% of R-square value. Followed by working environment which contribute 8.2%.